Bendamustine in combination with ofatumumab as first line treatment for elderly patients with mantle cell lymphoma: a phase II risk-adapted design. Issue 12 (15th October 2022) - Kumar, Anita; Casulo, Carla; Joffe, Erel; Moskowitz, Craig; Gerecitano, John; Moskowitz, Alison; Younes, Anas; Drullinsky, Pamela; Drill, Esther; Choma, Morgan; Grieve, Clare; Joseph, Ashlee; et al.
Abstract: This study evaluated ofatumumab (Ofa), an anti-CD20 monoclonal antibody, alone or with bendamustine (Benda), in transplant-ineligible patients with mantle cell lymphoma. Low-risk patients received Ofa monotherapy. Non-responders received subsequent treatment with Benda-Ofa. Six patients received Ofa monotherapy and 3 patients crossed over to Bend-Ofa. Twenty-four high-risk patients were initially treated with Benda-Ofa. The overall response rate for patients treated with Ofa monotherapy was 1/6 (17%) and 23/25 (92%) for patients treated with Benda-Ofa. With a median follow-up of 8.6 years, all Ofa patients progressed with a median progression-free survival (PFS) of 0.6 years (95% CI 0.31-NR) and remain alive. With a median follow-up of 6.3 years, Bend-Ofa treated patients had median PFS 2.5 years (95% CI 1.8-NR) and a median overall survival of 7.4 years (95% CI 5.8-NR). Benda-Ofa had a favorable adverse event profile and efficacy similar, but not clearly superior, to those reported for Benda-Rituximab.